Implementation of an integrated management system into a small building company - Giacomello, Humberto; Gonzalez Stumpf, Marcos Aurelio; Parisi Kern, Andrea (Revista de la Construcción. Journal of Construction, 2014)
Building firms has implanted tools and practices to improve their quality level. The integration between production and other management system is beneficial for achieving improvements in construction. However, in some cases, construction companies develop isolated management systems, and there are few research papers that describe this kind of application in small construction companies, which constitute the majority of building companies in Brazil. This paper presents the implantation of an integrated management system in a small construction company. The work includes the diagnosis of management system of the company, the proposition and applying of an integrated process, and the identification of outcomes. It was developed through observation of three building sites in Bento Gonçalves, a city on southern Brazil. On research process it were implanted tools on planning and control to management systems to short, medium, and large terms. After all, our results may conclude that there is viability to implant this system in small building companies, with waste reduction on the production process.